Manejo integrado del Kudzu (pueraria Lobata) en la agricultura - Ramírez Reátegui, Raydith (2012)
The objective of the present work is to evaluate integrated systems for planting as a source of altemative development, which would be of direct benefít to farmers, this way they will realize that these practices they agree and the benefíts they bring. The evaluated systems are the silvopastoriles and coverage systems, in both systems the kudzu is applied as principal or additional plant, obtaining like proved an almost perfect symbiosis that was reaching positively to the environment and certainly to the farmers who will be directly the major benefíciaries. After a previous evaluation of these two systems fínally proposed to the system as a model of Silvopastoril final planting, due to the adaptability of their productive characteristics, to its easy implementation of planting, and the environmental benefíts that you can bring as a result of the implementation of the same in the fiel d. This model is a complex system but simultaneously completely because in her plant, animal interact, man and because not to say environment, all that inside a harmonious system. It constitutes a food factor for the animals in difficult epochs, contributing with the production of milk and meat of cattle that he benefits directly to the farmers and . from the environmental point of view, is a potential credit for the soils improving this way the quality of the same one. Like all model introduced will have disadvantages, but depending on the care to be taken before, during and after planting these will be minimal and not interfere in a negative way in the results and the production.